Involvement of the Interferon-Regulated Antiviral Proteins PKR and RNase L in Reovirus-Induced Shutoff of Cellular Translation - Smith, Jennifer A. (American Society for Microbiology, 2005)
Cellular translation is inhibited following infection with most strains of reovirus, but the mechanisms responsible for this phenomenon remain to be elucidated. The extent of host shutoff varies in a strain-dependent manner; infection with the majority of strains leads to strong host shutoff, while infection with strain Dearing results in minimal inhibition of cellular translation. A genetic study with reassortant viruses and subsequent biochemical analyses led to the hypothesis that the interferon-induced, double-stranded RNA-activated protein kinase, PKR, is responsible for reovirus-induced host shutoff. To directly determine whether PKR is responsible for reovirus-induced host shutoff, we used a panel of reovirus strains and mouse embryo fibroblasts derived from knockout mice. This approach revealed that PKR contributes to but is not wholly responsible for reovirus-induced host shutoff. Studies with cells lacking RNase L, the endoribonuclease component of the interferon-regulated 2′,5′-oligoadenylate synthetase-RNase L system, demonstrated that RNase L also down-regulates cellular protein synthesis in reovirus-infected cells. In many viral systems, PKR and RNase L have well-characterized antiviral functions. An analysis of reovirus replication in cells lacking these molecules indicated that, while they contributed to host shutoff, neither PKR nor RNase L exerted an antiviral effect on reovirus growth. In fact, some strains of reovirus replicated more efficiently in the presence of PKR and RNase L than in their absence. Data presented in this report illustrate that the inhibition of cellular translation following reovirus infection is complex and involves multiple interferon-regulated gene products. In addition, our results suggest that reovirus has evolved effective mechanisms to avoid the actions of the interferon-stimulated antiviral pathways that include PKR and RNase L and may even benefit from their expression.